Co-localization of erythropoietin mRNA and ecto-5'-nucleotidase immunoreactivity in peritubular cells of rat renal cortex indicates that fibroblasts produce erythropoietin. - Bachmann, Sebastian; Le Hir, Michel; Eckardt, Kai-Uwe (Journal of histochemistry & cytochemistry, 1993)
In adults, the kidneys are the major site of production of the glycoprotein hormone erythropoietin (EPO), but the type of renal cell producing EPO has not yet been identified. In the present study we used non-radioactive in situ hybridization with a digoxigenin-labeled cRNA probe to localize cells that produce erythropoietin (EPO) in kidneys of anemic rats. Cryostat sections from both native and perfusion-fixed tissue were used. Cells containing EPO mRNA were found exclusively in the peritubular space of the renal cortex. Using high-resolution interference contrast optics, we found that cells expressing EPO mRNA were not associated with the lumina of peritubular capillaries but rather were located in the angles between adjacent tubules or between tubules and vessels. These spaces are predominantly occupied by resident interstitial fibroblasts and by their cytoplasmic processes. To further identify the type of cell containing EPO mRNA, a double-labeling protocol was established that permitted on the same tissue section both in situ hybridization for EPO mRNA and parallel immunolabeling of ecto-5'-nucleotidase (5'-Nu), a surface marker of peritubular interstitial fibroblasts. The combined labeling technique revealed that a clear majority of cells expressing EPO mRNA also displayed staining for anti-5'-Nu. Staining for EPO mRNA was localized in central perinuclear parts of the interstitial cells, whereas 5'-Nu label was present on the cell surface, including the cytoplasmic processes. These data indicate that peritubular fibroblasts are cellular sites for production of erythropoietin.
Gesehen am 04.12.2023